2014
DOI: 10.1016/j.physbeh.2014.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient selection by seven inbred mouse strains and three taste-related knockout strains

Abstract: Many animals thrive when given a choice of separate sources of macronutrients. How they do this is unknown. Here, we report some studies comparing the spontaneous choices between carbohydrate-and fat-containing food sources of seven inbred mouse strains (B6, BTBR, CBA, JF1, NZW, PWD and PWK) and three mouse models with genetic ablation of taste transduction components (T1R3, ITPR3 and CALHM1). For 8 days, each mouse could choose between sources of carbohydrate (CHO-P; sucrose-corn-starch) and fat (Fat-P; veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The inositol triphosphate receptor 3 gene ( Itpr3 ), was identified as responsible for the mouse tufted (tf) locus (Ellis et al 2013), which resulted with a change of the strain name from BTBR T + tf/J to BTBR T + Itpr3 tf /J. More importantly, the deletion within the Itpr3 gene was found to cause indifference of BTBR mice to sweet, Polycose, umami, bitter, and calcium tastes (Tordoff et al 2013), which in turn affects their food intake (preferential fat consumption, as compared to carbohydrate-rich diet, Tordoff et al 2014). In the light of these results, the reports of impaired social communication of food-preference in this strain (McFarlane et al 2008), as well as the use of BTBR mice to validate food reward based tasks (Martin et al 2014) need to be reconsidered.…”
Section: Altered Gene and Protein Expression In The Btbr Mousementioning
confidence: 99%
“…The inositol triphosphate receptor 3 gene ( Itpr3 ), was identified as responsible for the mouse tufted (tf) locus (Ellis et al 2013), which resulted with a change of the strain name from BTBR T + tf/J to BTBR T + Itpr3 tf /J. More importantly, the deletion within the Itpr3 gene was found to cause indifference of BTBR mice to sweet, Polycose, umami, bitter, and calcium tastes (Tordoff et al 2013), which in turn affects their food intake (preferential fat consumption, as compared to carbohydrate-rich diet, Tordoff et al 2014). In the light of these results, the reports of impaired social communication of food-preference in this strain (McFarlane et al 2008), as well as the use of BTBR mice to validate food reward based tasks (Martin et al 2014) need to be reconsidered.…”
Section: Altered Gene and Protein Expression In The Btbr Mousementioning
confidence: 99%
“…For example, it was reported that CALHM1 KOs were “visually indistinguishable” from their WT littermates (Vingtdeux et al 2011). However, a more detailed and longer term examinations found deficits in body mass, as well as in macronutrient intake, relative to control mice (Hellekant et al 2015; Tordoff et al 2014). Similar results have been observed with other KO models of gustatory transduction in the periphery (TRPM5 and T1R3 KOs; e.g., Damak et al 2013; Minaya 2014).…”
Section: Discussionmentioning
confidence: 82%